Dynamics of leukocyte inflammatory markers in patients with ST-elevation myocardial infarction depending on left ventricle ejection fraction - V. K. Tashchuk; R. A. Bota; M. V. O. Al Salama (Patologìâ)
Aim: to evaluate the dynamics of leukocyte inflammatory markers in patients with ST-elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) depending on ejection fraction of left ventricular (LV).